Caesarean Scar Endometriosis - Sedhain, Nesuma; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema K; Shrestha, Ranjana; Bhattachan, Kabin; Poudel, Rekha; Bajracharya, Nishma (Journal of Nepal Health Research Council, 2018)
Endometriosis is a common benign gynecologic disorder defined as the presence of endometrial glands and stroma outside of the normal location. The overall prevalence is 8–15% in women of reproductive age group. Scar endometriosis is a rare disease, and is difficult to diagnose. It is commonly seen following obstetrical and gynecological surgeries. The symptoms are non-specific, typically involving abdominal wall pain at the incision site at the time of menstruation and palpable tender mass in the incision site. The diagnosis is frequently made only after excision of the diseased tissue and its histological analysis. We present here a case of abdominal wall scar endometriosis in a woman who had undergone a caesarean section four years ago. Surgical excision led to the diagnosis of scar endometriosis. The pathogenesis, diagnosis and treatment of this rare condition are discussed. Keywords: Abdominal wall; caesarean section; painful scar; scar endometriosis.